SUPPLY CHAIN MANAGEMENT : STRATEGY, PLANNING, AND OPERATION - Chopra, Sunil (Pearson Education Limited, 2019)
Supply Chain Management introduces high-level strategy and concepts while giving students the practical tools necessary to solve supply chain problems. Using a strategic framework, students are guided through all of the key drivers of supply chain performance, including facilities, inventory, transportation, information, sourcing, and pricing. The 7th Edition, Global Edition, weaves in compelling case study examples to illustrate how good supply chain management offers a competitive advantage and how poor supply chain management can damage an organization’s performance. With this text, students gain a deeper understanding of supply chains and a firm grasp on the practical managerial levers that can improve supply chain performance